Circulating Air: Inspiration, Voice and Soul in Poetry and Song. Issue 1 (March 2018) - Kay, Sarah
Abstract : This paper proposes an alternative view to the influential one of air or breath as inspiration that produces an imagined inner vision of the desired object. Instead, it outlines a poetics where air and inspiration connect with voice, language and music, thereby privileging sound over sight. A genealogy for this account is traced through Aristotle and various treatises connected to him, and an example of its operation is discussed in a song by the troubadour Bernart Marti. Voice is theorized as a kind of sound, including non-human sound, made by striking air, which expresses the soul's passions and marks both the boundary and the connection between air and soul. Poetry and song form soundscapes whose implications exceed the acoustic.